Perancangan Mobile Game Edukasi Pengenalan Buah-Buahan untuk Sekolah Dasar - Michael David; Eunike Insani; Daniel Tumangger; Siti Aisyah (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2021)
The purpose of this research is to look into the design of an educational mobile game for the introduction of fruits in elementary schools. This fruit recognition educational mobile game is a modern learning application that uses Android technology to make learning more convenient anywhere and at any time. Learning activities are more effective when there are media that can attract the senses and attract interest, as there are image objects, attractive displays, and pronunciation of the letters of the alphabet in this educational mobile game. This game application also includes exercises to help you improve your learning spirit. This application employs a qualitative methodology. The goal of this study is to assist elementary school students who are having difficulty learning.